2019
DOI: 10.3390/app9245549
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Thermo-Mechanical Activation of Bentonite on the Mechanical and Durability Performance of Concrete

Abstract: Despite presenting a very high global warming toll, Portland cement concrete is the most widely used construction material in the world. The eco-efficiency, economy, and the overall mechanical and durability performances of concrete can be improved by incorporating supplementary cementitious materials (SCMs) as partial substitutions to ordinary Portland cement (OPC). Naturally found bentonite possesses pozzolanic properties and has very low carbon footprint compared to OPC. By applying activation techniques, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
(71 reference statements)
4
8
0
Order By: Relevance
“…The outcome of this research can be used for the evaluation of the effect of local waste mineral admixtures found in Pakistan on the properties of plain and fiber-reinforced concrete. A variety of natural and waste mineral admixtures are cheaply available in Pakistan, e.g., bentonite, metakaolin, rice husk ash, slag, fly ash, and silica fume [13,[55][56][57], but there is a lack of published information on the properties of these mineral admixtures in normal and fiber-reinforced concrete. To cope with the rising climate changes in Pakistan and surrounding regions, it is necessary to reduce the reliance of the concrete industry on cement production by supplementing the demand for cement with supplementary mineral admixtures.…”
Section: Research Significancementioning
confidence: 99%
“…The outcome of this research can be used for the evaluation of the effect of local waste mineral admixtures found in Pakistan on the properties of plain and fiber-reinforced concrete. A variety of natural and waste mineral admixtures are cheaply available in Pakistan, e.g., bentonite, metakaolin, rice husk ash, slag, fly ash, and silica fume [13,[55][56][57], but there is a lack of published information on the properties of these mineral admixtures in normal and fiber-reinforced concrete. To cope with the rising climate changes in Pakistan and surrounding regions, it is necessary to reduce the reliance of the concrete industry on cement production by supplementing the demand for cement with supplementary mineral admixtures.…”
Section: Research Significancementioning
confidence: 99%
“…The low-calcium bentonite is a naturally found pozzolana, rich in silica and alumina, that has been extensively used for many years to improve the mechanical and durability properties of conventional concrete [34,35]. Bentonite is an alumino-phyllosilicate clay, comprising mainly montmorillonite minerals and usually formed by the chemical weathering of volcanic ash in the presence of water.…”
Section: Introductionmentioning
confidence: 99%
“…The strength development of NP blended cement composite materials is dependent on the size of NP and its reaction capability which highly contribute to the strength development by reinforcing the microstructural matrix and forming binding hydrates that consume portlandite [13,15,90,[140][141][142]. At an early age, NP lowers the strength of the concrete mixture as Senhadji et al [99], but through longer ages, the pozzolanic reaction aids in more strength development than the control concrete mix [1,34,77,94,[143][144][145][146][147][148][149]. The amorphous silicate matrix actively reacts with portlandite to form a secondary C-S-H gel which mainly improves the microstructure and strength of the final hydrated cement matrix, which is mostly dependent on the hydration reaction of NP and cement phase [95,120,150].…”
Section: Effects On Mechanical Propertiesmentioning
confidence: 99%